Economic evaluation and environmental benefits of biofuel: an Indian perspective. (13th December 2007) - Chandel, Anuj Kumar; Kapoor, Rajeev Kumar; Lakshmi Narasu, M.; Viswadevan, Viswajith; Kumaran, S.G.; Rudravaram, Ravinder; Rao, L.; Tripathi, K.K.; Lal, Banwari; Kuhad, R.C.
Biomass based fuel technologies are rapidly developing and the barriers in implementing such technologies are being identified to achieve their widespread commercialisation. The two most common biofuels are biodiesel and bioethanol. About 500 million litres of ethanol is required in India itself for 10% blending to gasoline. Indian Planning Commission sees tremendous potential in Jatropha curcus and has supported through various government agencies nationwide programmes to cultivate using wastes/degraded lands. Biofuel policy might capitalise on the production of biofuels supporting rural economic development and sustainable agriculture. This paper discusses the economic and environmental aspects of Biofuel specially in Indian perspective.